2010
DOI: 10.1007/s12224-010-9082-5
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Growth Strategies Along Flooding and Grazing Gradients in Atlantic Coastal Meadows

Abstract: International audienceSpecific composition and species clonal traits were characterized along combined flooding and grazing gradients to answer two questions. i) To what extent does the interaction of flooding and grazing influence the clonal characteristics of the vegetation? ii) Are the effects of both environmental factors independent or interactive? This study was carried out in a wet meadow along the Atlantic coast (France). Three plant communities (hygrophilous, mesohygrophilous and mesophilous) were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
(65 reference statements)
1
17
0
Order By: Relevance
“…The hypothesis by Jónsdóttir and Watson (1997), i.e., that plants with splitting clones prevail in nutrient-rich conditions whereas integrators in nutrient-poor conditions, was supported by Rusch et al (2011). Using the results from other studies here (Wellstein and Kuss 2011;Klimešová et al 2011;Benot et al 2011) we could slightly expand the hypothesis that not only low versus high nutrients but also dry versus wet conditions lead to the same pattern of persistence of connection between ramets. As another finding, lateral spread of integrators in dry-and nutrient-poor conditions seems to be less extensive than previously expected (see also van Groenendael et al 1996;Halassy et al 2005).…”
Section: Key Findingssupporting
confidence: 57%
See 2 more Smart Citations
“…The hypothesis by Jónsdóttir and Watson (1997), i.e., that plants with splitting clones prevail in nutrient-rich conditions whereas integrators in nutrient-poor conditions, was supported by Rusch et al (2011). Using the results from other studies here (Wellstein and Kuss 2011;Klimešová et al 2011;Benot et al 2011) we could slightly expand the hypothesis that not only low versus high nutrients but also dry versus wet conditions lead to the same pattern of persistence of connection between ramets. As another finding, lateral spread of integrators in dry-and nutrient-poor conditions seems to be less extensive than previously expected (see also van Groenendael et al 1996;Halassy et al 2005).…”
Section: Key Findingssupporting
confidence: 57%
“…In another study, Benot et al (2011) supported the idea that a bud bank located belowground is important for grazed meadows (Klimešová and Klimeš 2007) but stressed that its functional role in response to grazing can be different in response to the prevailing abiotic conditions. Martínková et al (2011) found that a bud bank on roots of short-lived monocarps may affect their distribution and habitat preferences (Klimešová and Klimeš 2003) and Montserrat-Martí et al (2011) presented a conceptual model on the relationship between bud protection of chamaephytes and climate, which could be further tested in other regions of the world.…”
Section: Key Findingsmentioning
confidence: 92%
See 1 more Smart Citation
“…; Benot et al. ), limitation of internode length (Amiaud et al. ) and fragmentation of clone patches (Charpentier et al.…”
Section: Introductionmentioning
confidence: 99%
“…The number of ramets within a genet and overall clone circumference have been used to measure architectural variability (Doust, 1991;Cain & Damman, 1997;Price & Marshall, 1999;Sultan, 2000;Benot et al, 2011). Clone circumference, commonly used in studies of architectural variability, can also be used to analyze population structure, where size is taken as a proxy for time or developmental stage (Condit et al, 1998;Lykke, 1998).…”
Section: Introductionmentioning
confidence: 99%